2023
DOI: 10.1186/s12883-023-03163-0
|View full text |Cite
|
Sign up to set email alerts
|

Mobile health to promote physical activity in people post stroke or transient ischemic attack – study protocol for a feasibility randomised controlled trial

Abstract: Background Physical activity is essential to improve health and reduce the risk of recurrence of stroke or transient ischemic attack (TIA). Still, people post stroke or TIA are often physically inactive and the availability of physical activity promotion services are often limited. This study builds on an existing Australian telehealth-delivered programme (i-REBOUND– Let’s get moving) which provides support for home-based physical activity for people post stroke or TIA. The aim of this study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 56 publications
0
10
1
Order By: Relevance
“…Prescribed video recorded exercises are to our knowledge mostly generic recordings performed by healthy individuals without any deficits, which can affect stroke survivors’ motivation and make it hard to relate to as mentioned in this study. Although, a recent study protocol describe the use of people with stroke-related disabilities in their prescribed instructional generic video recordings to promote physical activity among stroke survivors [ 62 ], the results from our study indicate that recordings of the stroke survivor themselves support the experience of ‘clarity’, ‘necessity’, ‘ableness’, and a sense of progress.…”
Section: Discussioncontrasting
confidence: 58%
“…Prescribed video recorded exercises are to our knowledge mostly generic recordings performed by healthy individuals without any deficits, which can affect stroke survivors’ motivation and make it hard to relate to as mentioned in this study. Although, a recent study protocol describe the use of people with stroke-related disabilities in their prescribed instructional generic video recordings to promote physical activity among stroke survivors [ 62 ], the results from our study indicate that recordings of the stroke survivor themselves support the experience of ‘clarity’, ‘necessity’, ‘ableness’, and a sense of progress.…”
Section: Discussioncontrasting
confidence: 58%
“…Among the included studies ( Table 2 ), five were conducted in Australia ( 35 , 36 , 42 , 44 , 45 ) two in China ( 47 , 48 ), two in Israel ( 43 , 50 ), one in the Netherlands ( 37 ) one in Norway ( 38 ), one in France ( 40 ) one in Denmark ( 39 ), one in Spain ( 41 ) one in Thailand ( 46 ), one in Ghana ( 49 ), and one in Sweden ( 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…These past performances can serve as potent influences in cultivating self-efficacy. In this context, several studies have been identified that applied strategies such as the establishment of a therapeutic alliance ( 39 , 41 , 44 , 47 , 48 , 50 ), enhancing health literacy ( 35 37 , 40 42 , 44 49 , 51 ), setting achievable goals ( 38 , 40 42 , 44 48 , 50 , 51 ), personalizing rehabilitation programs ( 37 42 , 44 , 46 – 49 , 51 ), and honing problem-solving skills ( 39 , 42 47 , 50 , 51 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations